2021
DOI: 10.1002/macp.202100096
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Drug‐Loaded Graphene Oxide‐Based Nanocarrier into Electrospun Pullulan Nanofibers for Potential Local Chemotherapy of Breast Cancer

Abstract: With the high rate of mortality associated with breast cancer among women, breast cancer treatment has attracted great deal of attention globally. To reduce the exposure of body organs to high cytotoxicity of the common chemotherapeutic drugs, local co‐delivery of selected chemotherapeutics has emerged as a solution. In this work, an electrospun composite including a co‐drug‐loaded graphene oxide‐based nanocarrier is fabricated for local anticancer applications. To increase dispersion and cellular uptake of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Paclitaxel (PTX) and CUR drugs were loaded into a nanocarrier consisting of GO-grafted poly(epichlorohydrin) and OH groups that were grafted with hyperbranched polyglycerol and encapsulated into pullulan nanofibers using electrospinning, which exhibited sustained release in a medium with pH 7.4, and this drug delivery system has the potential to be used for local chemotherapeutic applications [ 138 ]. DOX-loaded Pluronic ® F127/GO nanohybride induced a higher apoptosis rate of U251 cells than that of free DOX (12.27 ± 0.06% vs. 8.20 ± 0.06%), affected the mitogen-activated protein kinase (MAPK) signaling pathway, and induced the intrinsic pathway, of apoptosis for the activation of caspase-3 in U251 cells [ 139 ].…”
Section: Gbns As Drugs and Nanocarriersmentioning
confidence: 99%
“…Paclitaxel (PTX) and CUR drugs were loaded into a nanocarrier consisting of GO-grafted poly(epichlorohydrin) and OH groups that were grafted with hyperbranched polyglycerol and encapsulated into pullulan nanofibers using electrospinning, which exhibited sustained release in a medium with pH 7.4, and this drug delivery system has the potential to be used for local chemotherapeutic applications [ 138 ]. DOX-loaded Pluronic ® F127/GO nanohybride induced a higher apoptosis rate of U251 cells than that of free DOX (12.27 ± 0.06% vs. 8.20 ± 0.06%), affected the mitogen-activated protein kinase (MAPK) signaling pathway, and induced the intrinsic pathway, of apoptosis for the activation of caspase-3 in U251 cells [ 139 ].…”
Section: Gbns As Drugs and Nanocarriersmentioning
confidence: 99%
“…Differently from other polysaccharide types, PULL can easily dissolve in water thanks to the low degree of hydrogen bonding in the structure . It has been previously reported that electrospun nanofibrous webs of PULL can be used for drug transportation, filtration, medical scaffolds, and food packaging. PULL can also be electrospun into NFs along with the combination of a variety of drug molecules to create FDDSs. , …”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Amiji et al reported a flaxseed-oil-containing nanoemulsion formulation to encapsulate PTX and CUR to overcome the MDR in ovarian cancer [ 12 ]. There have been many carrier-based formulations for the codelivery of PTX and CUR, including polymeric systems [ 13 , 14 , 15 ], liposomes, niosomes [ 16 ], cyclodextrins [ 17 ], and graphene oxide [ 18 ], but these all suffer from low drug loadings and could pose challenges due to the nontherapeutic carrier mass compositions and the unknown long-term toxicities of the carrier components [ 3 ].…”
Section: Introductionmentioning
confidence: 99%